THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND PACKAGING ON CUSTOMER LOYALTY OF KOPI MUTIARA KEDIRI - Alam, Mutiara Tirta; Sutanto, J.E. (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The purpose of this study was to test and analyze the effect of product quality, price, and packaging on customer loyalty for Mutiara Kediri Coffee. This research uses a quantitative approach where the research data is collected through a questionnaire. The research sample of 119 respondents was taken randomly using purposive sampling technique. The sample criteria used are customers who have bought Mutiara Coffee more than 2 times. The analytical method used in this study is multiple linear regression analysis. Data were collected through a Likert scale questionnaire to measure customer perceptions of product quality, price, packaging, and loyalty. Regression analysis reveals that product quality, price, and packaging all have a significant positive effect on customer loyalty. Specifically, higher product quality fosters greater commitment and repeat purchases, while competitive pricing and attractive, functional packaging also contribute to increased loyalty. The study highlights that each of these factors independently influences customer behavior, and together, they significantly shape long-term customer retention. Further research is suggested to explore other factors, such as social media presence, that might influence customer behavior in the food and beverage sector.